The aesthetics of fan fiction : an ontological study of ‘Rosario+Vampire’ fanon in Fanfiction.net. - Mohamad Abdul Halim Aziz. (2013)
Fan fiction. The term itself would bring shivers of incredulity in many professional writers. Commonly thought of as pleasure-deriving work by a person who is a, “hobbyist, knowledgeable or otherwise, someone who does not make a living from his or her field of interest, a layperson, lacking credentials, a dabbler.” (Keen, 36), derivative works which fan fiction actually is not a new phenomenon. Instead it is like a hole in a tank that is slowly getting bigger such that people are finally seeing its impact on the newly carpeted floor that is the literary world. Why is fan fiction given a negative connotation? Is it as simple as it is made out to be? Can it be anything more than a label of condescension? This thesis aims to answer just that by identifying the ways in how Internet fan fiction have transgressed the narratives of their canon and in doing so to analyse the ontological aspects of fan fiction.